Biomimetic peptide enriched nonwoven scaffolds promote calcium phosphate mineralisation. Issue 47 (29th July 2020) - Gharaei, Robabeh; Tronci, Giuseppe; Goswami, Parikshit; Davies, Robert P. Wynn; Kirkham, Jennifer; Russell, Stephen J.
Abstract : A structurally robust electrospun peptide-enriched scaffold, with controlled peptide release behaviour, supports nucleation and growth of hydroxyapatite minerals in vitro . Abstract : Cell-free translational strategies are needed to accelerate the repair of mineralised tissues, particularly large bone defects, using minimally invasive approaches. Regenerative bone scaffolds should ideally mimic aspects of the tissue's ECM over multiple length scales and enable surgical handling and fixation during implantation in vivo . Leveraging the knowledge gained with bioactive self-assembling peptides (SAPs) and SAP-enriched electrospun fibres, we presented a cell free approach for promoting mineralisation via apatite deposition and crystal growth, in vitro, of SAP-enriched nonwoven scaffolds. The nonwoven scaffold was made by electrospinning poly(ε-caprolactone) (PCL) in the presence of either peptide P11 -4 (Ac-QQRFEWEFEQQ-Am) or P11 -8 (Ac QQRFOWOFEQQ-Am), in light of the polymer's fibre forming capability and its hydrolytic degradability as well as the well-known apatite nucleating capability of SAPs. The 11-residue family of peptides (P11 - X ) has the ability to self-assemble into β-sheet ordered structures at the nano-scale and to generate hydrogels at the macroscopic scale, some of which are capable of promoting biomineralisation due to their apatite-nucleating capability. Both variants of SAP-enriched nonwoven used in this study were proven to be biocompatible with murine fibroblasts and supported nucleation and growth of apatite minerals in simulated body fluid (SBF) in vitro . The fibrous nonwoven provided a structurally robust scaffold, with the capability to control SAP release behaviour. Up to 75% of P11 -4 and 45% of P11 -8 were retained in the fibres after 7 day incubation in aqueous solution at pH 7.4. The encapsulation of SAP in a nonwoven system with apatite-forming as well as localised and long-term SAP delivery capabilities is appealing as a potential means of achieving cost-effective bone repair therapy for critical size defects.